2011
DOI: 10.1590/s1413-41522011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Glucose effect on degradation kinetics of methyl parathion by filamentous fungi species Aspergilus Niger AN400

Abstract: This study evaluated the glucose effect on the removal of methyl parathion by Aspergillus niger AN400. The study was conducted in two stages: toxicity tests on plates and assays in flasks, under an agitation of 200 rpm. The methyl parathion concentrations in the toxicity test ranged from 0.075 to 60 mg/L. The second stage consisted on evaluating reactors: six control reactors with methyl parathion solution; six reactors with fungi and methyl parathion, and six reactors containing fungi, methyl parathion, and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…The optimum pH for paracetamol degradation was 6.0 for both fungal species. This result is consistent with that by Marinho et al, 28 who reported that the optimum pH for atrazine degradation by A. niger was 5. Also, Govarthanan et al, 26 recorded that decane degradation by Penicillium sp.…”
Section: Figure 5: Paracetamol Degradation Curve By F1supporting
confidence: 93%
“…The optimum pH for paracetamol degradation was 6.0 for both fungal species. This result is consistent with that by Marinho et al, 28 who reported that the optimum pH for atrazine degradation by A. niger was 5. Also, Govarthanan et al, 26 recorded that decane degradation by Penicillium sp.…”
Section: Figure 5: Paracetamol Degradation Curve By F1supporting
confidence: 93%
“…Biodegradation of organophosphorus pesticides by organophosphorus hydrolase has been reported by Richins et al (1997). Marinho et al (2011) reported that the presence of glucose in the medium helped the removal of the pollutant. Fungus possesses several enzymatic systems such as glucose oxidase, catalase, lactanase, cytochrome P450 monooxygenase and ligninolytic enzymes.…”
Section: Hplc Analysismentioning
confidence: 93%
“…Its system plays a central role in the oxidative metabolism as well as in the detoxification of xenobiotics. The enzyme catalyses the epoxidation of the aromatic ring, producing arene oxides that are formed through the epoxide hydrolase trans-dihydrodiols or rearranged nonenzymatically to form phenols (Marinho et al 2011) Therefore, this enzymatic system must have been activated, promoting the partial degradation of methylparathion. The enzymatic action of the fungus may have been responsible for the degradation of methylparathion.…”
Section: Hplc Analysismentioning
confidence: 99%
“…Marinho et al [ 52 ] also hypothesized that the addition of glucose should improve the efficiency of A. niger to biodegrade methyl parathion in batch reactors. Since the presence of glucose increased the conversion rate, it proved indispensable for the efficient removal of methyl parathion by submerged culture of fungus.…”
Section: Degradation Of Organophosphorus Pesticides By Aspe...mentioning
confidence: 99%